Full-endoscopic Uniportal Odontoidectomy and Decompression of the Anterior Cervicomedullary Junction Using the Retropharyngeal Approach. Issue 15 (1st August 2018) - Ruetten, Sebastian; Hahn, Patrick; Oezdemir, Semih; Baraliakos, Xenophon; Merk, Harry; Godolias, Georgios; Komp, Martin
Abstract : Study Design: A study of a series of consecutive full-endoscopic uniportal decompressions of the anterior craniocervical junction with retropharyngeal approach. Objective: The aim of this study was to evaluate the direct anterior decompression of the craniocervical junction in patients with bulbomedullary compression using a full-endoscopic uniportal technique via an anterolateral retropharyngeal approach. Summary of Background Data: Acute or progressive myelopathy may necessitate direct anterior decompression of the craniocervical junction and odontoidectomy. Different techniques with individual advantages and disadvantages can be used. In addition to the gold standard – the transoral approach – there is increasing experience with the endoscopic transnasal technique. Other alternative procedures are also being developed. Methods: Between 2013 and 2016, eight patients with basilar impression, retrodental pannus, or retrodental infection were operated in the full-endoscopic uniportal technique with a retropharyngeal approach. Anterior decompression of the bulbomedullary junction with odontoidectomy was performed. All patients additionally underwent posterior stabilization. Imaging and clinical data were collected in follow-up examinations for 1 year. Results: The bulbomedullary junction was adequately decompressed. No problems due to swelling of pharyngeal soft tissue occurred. One patient required revision due to secondary bleeding. No other complications were observed. All patients had a good clinical outcome with stable regression of the myelopathy symptoms and/or healing of the infection. The imaging follow-up showed sufficient decompression of bone and soft tissue in all cases. No evidence was found of increasing instability or failure of posterior fusion. Conclusion: In the operated patients, the full-endoscopic uniportal surgical technique with anterior retropharyngeal approach was found to be a sufficient and minimally invasive method with the known advantages of an endoscopic procedure under continuous irrigation. It should not be viewed only as competition for other surgical techniques – due to its individual technical parameters, it can also be considered to be an alternative or complementary procedure. Level of Evidence: 4